THE SHARIAH ADVISORY COUNCIL OF SECURITIES COMMISSION MALAYSIA RESOLUTION ON MIXED COMPANIES: A JURISTIC APPRAISAL - Muhammad Hamdan Syafieq Ahmad; Nor Faezah Ghazi Ahmad; Wan Noor Hazlina Wan Jusoh (Journal of Islamic, Social, Economics and Development, 2022)
Mixed companies has been a topic of discussion by Islamic scholars for centuries. Today, the issue of mixed companies is applied to Muslim’s participation in stock investment of a company which has impermissible elements in its business. Shariah Advisory Council (SAC) of Securities Commission Malaysia (SC) has issued its resolution on this matter. This paper’s intent is to critically analyze, provide juristic comments and discuss the aforementioned resolution. This paper employs library research focusing on classical Shariah books and found that the arguments provided by the SAC of SC in its resolution are arguable due to clear evidence from Al-Quran and Sunnah and since there are other options available to avoid involvement of Muslim in impermissible activities especially riba and liquor. This paper has also provided some considerable suggestions for SAC of SC to handle this issue. One possible way is to create a new subsidiary for the mixed company and then sells the minority interest to engage in prohibited activities to the public through an IPO. So, those minorities who want to invest in prohibited activities can buy this newly issued share. Thus, making a clear separation between permissible shares and the non-permissible ones. This will help to encourage Muslims to invest and concentrate their wealth only on permissible investments.